COMBINING ABILITY ANALYSIS FOR TUBER YIELD AND LATE BLIGHT IN POTATO - Kumar, Vinod; Gopal, Jai; Dhiman, K R (Potato Journal, 2013)
A study was conducted during 2003-04 and 2004-05 on 44 crosses obtained from 11 x 4 factorial mating design to evaluate them for tuber yield and late blight in seedling (transplanted) and seedling-tuber crops. Non-additive gene action was found to be important in the inheritance of tuber yield and its components and late blight resistance. Progeny means of crosses involving both or at least one parent with good gca were, in general, higher than other cross combinations for various character. Superior parents and crosses were identified. Based on mean and sca in both generations, crosses CP 2181 x CP 2407 and CP 3072 x CP 2351 were found promising for tuber yield.